KONSTRUKSI KELUARGA PADA PELAKSANAAN PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 DI DESA CIBANGKONG KABUPATEN BANYUMAS - Agusty, Awalia Hening (Spektrum Analisis Kebijakan Pendidikan, 2021)
This study aims: to describe how families construct online learning policies are reviewed from the differentiation of economic background as well as supporting factors and inhibitory factors. The research approach uses descriptive qualitative. The subjects of the study were parents who had primary school-age children. Data collection techniques using observations, interviews, documentation. The data is analyzed using interactive methods. The validity of the data is tested by triangulation techniques and source triangulation. The results of the study: (1) Family construction on online learning, parents with upper-middle economic level can access education easily, while parents with lower economic levels have difficulty in accessing education. Parent role: Pre-learning: not playing an active role, Learning implementation: active role, Post-Learning: passive-active. (2) Supporting factors: availability of online learning tools, availability of WiFi as internet source, including tutoring children, support from family. Inhibitory factors: inadequate facilities, teacher's lack of creativity in designing online learning, changes in the learning environment make children lose learning motivation, lack of parental knowledge.Â Keywords: Family Construction, Economic Background, Online Learning